중국 진·한(秦·漢) 시대의 전통 와당 문양을 활용된 심벌 디자인에 관한 연구 -베이징 지역의 공공시설에 중심으로 - 사무하; Xie Wu Xia; 박용진; Park Yong Jin; 김진성; Kim Jin Sung (기초조형학연구, 2017)
중국 고대 문화에는 전통 문양이 다양하게 형성 되어 있으며 이것이 중국 민족의 역사와 사회의 발전을 대표하는 상징일 뿐만 아니라 국가적 문화자산이며 세계적으로도 문화 예술적 가치가 있다. 중국 진·한(秦·漢) 시대의 통치자가 6개국을 통일한 후에 대규모 토목 공사를 통해 와당(기와)을 대량 사용하여 와당 문양의 형태 및 주제를 다양하게 발전시켰다. 와당문양은 장수와 부귀 등 여러 가지 의미를 상징하기 때문에 예로부터 사람들의 사랑을 많이 받아오고 있다. 관련된 선행연구를 살펴보면, 와당의 역사적 발전이나 건축 소재로 장식에 대한 연구를 많이 하였다. 그러나 그 시대의 문화 배경에서 와당문양은 독특한 예술 품격을 형성하여, 차별성을 보여주고 있기 때문에 현대의 디자인에 적용할 수 있는 요소가 많다. 그래서 문양의 풍부한 디자인 요소가 현대디자인 분야에 어떻게 적용하게 되는지 많은 연구가 필요하다. 본 연구는 중국 진·한(秦·漢) 시대의 전통 와당 문화 요소의 현대적 적용을 중심으로 베이징 지역에 있는 의료, 교육문화에 관한 공공시설 심벌디자인에 적용된 사례를 분석하였다. 이론적 고찰을 통해 와당 문양의 기원 및 발전을 파악하고 종류나 특징과 같은 표현 형식을 분석하였다. 와당 문양 및 공공시설 심벌디자인의 관계를 검토하고 와당문양이 공공시설 심벌디자인에 적용된 현황 분석을 통해 공공시설의 심벌디자인에 적용된 와당문양이 어떠한 특성을 가지는지에 대해서 연계하여 해석하고자 한다. 분석된 연구 결과를 토대로 와당 문양을 공공시설 심벌디자인에 적용하는 방법을 찾으려 하였으며, 현대 디자인에 전통 와당 문양을 잘 적용할 수 있는 디자인 가이드라인을 구축하는 것을 목적을 두고 연구하였다. In Chinese traditional culture, the traditional pattern, with full of variety and brilliance, represents not only Chinese nation`s long history as well as social development, but also a great treasure to global art and culture. Eaves tile began to be put into use widely, because the whole nation went in for large-scale construction after it was united as one in Qin and Han dynasties. Therefore, more and more decorative patterns and themes were created, when eaves tiles reached their greatest prosperity in that period. Different patterns corresponded to different wishes, such as longevity, wealth and safety. As a result, eaves tiles were popular among people in all ages. Most academic researches have focused on the history of tiles and their usage as building materials. However, influenced by the history and culture, eaves tile pattern in Qin and Han Dynasties has formed its unique artistic style which can be applied in the modern design. Therefore, the better application and combination of traditional art and modern culture is a valuable research worth studying. In order to study the method of applying eaves tile patterns to the modern design, this paper will analyze cases about the usage of tile patterns in public sings(logo) of medical and educational facilities in Beijing. Firstly, the origin , development, types and characteristics of eaves tiles will be studied according to theoretical research. Then, this paper will analyze the relationship between tile pattern and public facilities logo design. Through the analysis of the existing cases, the techniques and methods of using tile patterns in the design of public facilities can be concluded. Meanwhile, guidelines about how to apply eaves tile pattern could be better put forward in the future.